Christian (CJ) Johnson: capstone - Johnson, Christian, artist (Colorado State University. Libraries, 2019)
The artist's statement: The focus of my photographic practice and research revolves around exploring abstract concepts, philosophy, and ideas. Concepts such as Liminality, Aporia, and Apeiron interest me because they are concepts that we as humans all experience and, but don't address and acknowledge very often. I use Photography to express these ideas and emotions to bring attention to them and portray them using photography which is a medium that is not commonly known for being used abstractly.To achieve this, I use strategies such as photo manipulation and light painting to give my art an abstract and surreal look in attempt not to fool people, but to make people wonder and ask me how the work is made and to give form to emotions and experiences that would not have form otherwise.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: photography